Social Transformation of Kazakhstan Society in the System of Higher Education - Shormanbayeva, D.G.; Ivleva, E.N.; Seydinova, М.А. (Ye.A.Buketov Karaganda State University Publ., 2019)
The objective of this research is to study the attitude of students to social and cultural values of modern education system. The following tasks were determined: attitude of students to commercialization of the education system and its consequences; definition of the main social and cultural values of modern education; study of student identification grounds. Academic mobility was monitored among Bachelor students. According to the research results, we made the following conclusions: Currently, trends of westernization and commercialization of education are emerging. Students focus on pragmatic aspects of their education. The principles of individual freedom and self-realization dominate the principles of collectivism, ideological conviction and consciousness in the training process. The authors came to the conclusion that in modern conditions, updating of education content implies theoretically and practically justified transition to a humanitarian paradigm of education development, the measure and center of which is a person. The humanitarian paradigm of education development implies its humanitarization and humanization. The basis of this process integrity is spiritual component of education that presupposes a philosophical understanding of human being and problems of educating spirituality as the highest degree of human development. Thus, the education and educational programs quality must be assessed, first of all, by the depth of disclosing abilities of a human as a creative person.
Жоғары білім беру жүйесіндегі қазақстандық қоғамды əлеуметтік трансформациялау
Социальная трансформация казахстанского общества в системе высшего образования
Keywords: higher education; commercialization of education; academic mobility; international mobility; humanization; humanization